HALYTSKA KENASA (1836–1985): HISTORICAL AND ARCHITECTURAL ASPECTS - KOZELKIVSKYI, Volodymyr; CHEMERYNSKYI, Andriy (Halych. Scientific work collection, 2020)
The article is devoted to the historical and architectural study of the Karaite kenasa in Halych. For the first time, new archival and graphic materials about little known facts from the history of the shrine are introduced into scientific circulation. The architectural description of the building is made and its hypothetical plans are fulfilled. Saved sacral inventory is described.